9x+3y=27

Subtract 9x from both sides of the equation.

3y=27-9x

Divide each term in 3y=27-9x by 3.

3y3=273+-9×3

Cancel the common factor of 3.

Cancel the common factor.

3y3=273+-9×3

Divide y by 1.

y=273+-9×3

y=273+-9×3

Simplify each term.

Divide 27 by 3.

y=9+-9×3

Cancel the common factor of -9 and 3.

Factor 3 out of -9x.

y=9+3(-3x)3

Cancel the common factors.

Factor 3 out of 3.

y=9+3(-3x)3(1)

Cancel the common factor.

y=9+3(-3x)3⋅1

Rewrite the expression.

y=9+-3×1

Divide -3x by 1.

y=9-3x

y=9-3x

y=9-3x

y=9-3x

y=9-3x

The given equation y=9-3x can not be written as y=kx2, so y doesn’t vary directly with x2.

y doesn’t vary directly with x

Find the Quadratic Constant of Variation 9x+3y=27